Major Economic Trends Shaping the Future: Digital Transformation, Globalization, and Sustainability - Udenia, Sara (Journal of Global Economy, Business and Finance, 2025)
This article explores the significant economic trends currently shaping our global landscape, including digital transformation, globalization, sustainability, demographic shifts, and the rise of the experience economy. It examines how technological advancements, policy changes, and shifts in consumer behavior are driving these trends and their implications for businesses, policymakers, and individuals. As the world becomes more interconnected and dynamic, understanding these trends is crucial for making informed decisions and fostering resilience in an evolving economy. The article also discusses the challenges and opportunities presented by these trends, emphasizing the importance of innovation, adaptability, and sustainability in navigating the future.